Effects of methylamino acids on growth performance of swine in different stages - ZOU Xiao-ting; XU Zi-rong; WANG Yi-zhen (浙江大学学报. 农业与生命科学版, 2002)
This trial was conducted to investigate the effects of two kind of methylamino acids on growth performance of swine in different stages, and approach the mechanism involved. The results showed that a diet supplemented with 50 mg/kg N-methyl-D, Laspartate. improved performance of young piglets as well as growing and finishing pigs, and best result was obtained at the finishing stage, during which the average daily gain increased by 9.65% (P<0.05), and feed grain ratio decreased by 9.59% (P<0.05). Addition of 1000 mg/kg betaine into the diet also improved performance of swine, the growing swine stage being most suitable, which increased average daily gain by 13.20% (P<0.05), and decreased feed grain ratio by 7.93% (P<0.05). Study on the mechanism indicated that this two kind methylamino acids caused remarkable increase in the serum level of T3, the growth hormone and IGF-1, and uprised cAMP concentration in pituitary and adrenal gland of swine in various stages. It was concluded that methylamino acids might regulate neuroendcrine, stimulate growth hormone and IGF-1 secretion, and improve growth performance of swine.